1999
DOI: 10.1146/annurev.immunol.17.1.829
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the T Cell Repertoire

Abstract: Advances in gene technology have allowed the manipulation of molecular interactions that shape the T cell repertoire. Although recognized as fundamental aspects of T lymphocyte development, only recently have the mechanisms governing positive and negative selection been examined at a molecular level. Positive selection refers to the active process of rescuing MHC-restricted thymocytes from programmed cell death. Negative selection refers to the deletion or inactivation of potentially autoreactive thymocytes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
329
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 451 publications
(333 citation statements)
references
References 291 publications
2
329
0
2
Order By: Relevance
“…26,27 Following successful antigen receptor rearrangement, signals from the pre-T-cell receptors (pre-TCRs) or pre-B-cell receptors (preBCRs) signal the lymphocytes to promote the survival of the progenitors and induce their further differentiation. 28,29 T-lymphocyte progenitors that express a functional receptor are further subjected to both positive and negative selection to ensure that a functional receptor exists while eliminating those cells with self-reactive antigen receptors, which could be dangerous due to the potential for autoimmunity ( Figure 3). 30 When the avidity of interaction of the TCR and endogenous major histocompatibility complex (MHC) molecules is low, T-cell progenitors fail to be positively selected and undergo apoptosis.…”
Section: The Bcl-2 Familymentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Following successful antigen receptor rearrangement, signals from the pre-T-cell receptors (pre-TCRs) or pre-B-cell receptors (preBCRs) signal the lymphocytes to promote the survival of the progenitors and induce their further differentiation. 28,29 T-lymphocyte progenitors that express a functional receptor are further subjected to both positive and negative selection to ensure that a functional receptor exists while eliminating those cells with self-reactive antigen receptors, which could be dangerous due to the potential for autoimmunity ( Figure 3). 30 When the avidity of interaction of the TCR and endogenous major histocompatibility complex (MHC) molecules is low, T-cell progenitors fail to be positively selected and undergo apoptosis.…”
Section: The Bcl-2 Familymentioning
confidence: 99%
“…28 This complex is absolutely required for thymocyte development as mice lacking any of the components of the pre-TCR are blocked from further differentiation and undergo cell death (Figure 3). 52 Thus, the pre-TCR complex is essential not only for stimulating cell proliferation and further Signals transmitted through the pre-TCR primarily utilize the NF-kB signaling cascade to mediate the survival of developing T-lymphocytes.…”
Section: Antiapoptotic A1 In Pre-tcr Selectionmentioning
confidence: 99%
“…It has been shown that DP thymocytes can be positively selected by low-avidity interactions [24]. It has also been found that DP thymocytes and TCR int CD4 low CD8 low CD69 high (intermediate) thymocytes are equally susceptible to highavidity TCR stimuli that result in negative selection [23,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The developmental fate of maturing T cells depends on the type of pMHC-generated signal encountered in the thymus. Several groups have used peptides added to fetal thymic organ culture (FTOC) to study how peptides affect differentiation, finding that strong agonists delete the CD4 ϩ 8 ϩ "double-positive" thymocytes (reviewed in (1,2)). However, addition of certain weak agonist or antagonist ligands can result in positive selection, leading to the development of CD8 ϩ "single positive" cells (1,2).…”
mentioning
confidence: 99%